Cape Verde - Debt Management Performance Assessment (DeMPA) - World Bank (Washington, DC, 2022)
A World Bank mission undertook applied the Debt Management Performance Assessment (DeMPA) methodology to evaluate the government’s debt management (DM) capacity and institutions in Cabo Verde during March 28 to April 5, 2022. The assessment covers the legal, institutional, and regulatory framework governing DM. The primary counterpart was the Ministry of Finance (MoF) and within it, the Department of the National Treasury / Financial Operations Service which is the main DM office for the central government. The mission identified DM strengths and areas in need of reform, which are useful for measuring progress in DM capacity, supporting policy dialog with the authorities in the context of the second series of the Development Policy Financing operation (DPF). The policy dialogue helped to build on what has changed since the 2016 DeMPA and discussing persisting gaps in government debt management practices. Reducing debt vulnerabilities is an urgent priority for the government of Cabo Verde and would require a combination of debt reprofiling, higher economic growth and fiscal consolidation. With limited space to borrow, it would also require effective Debt Management.